Special Exercises after Weight Loss and its Effect on Skin Wrinkles and Body Beauty - Hussein Hassoun Abbas (Journal of Global Pharma Technology, 2018)
Many individuals, especially in these days, suffer from weight gain due to lack of movement and intake of food. They are not burned by exercise, which generates some wrinkles in the body. The researchers tried to find a suitable training program according to the characteristics of the research sample based on diversity. The use of exercises and the use of means and tools, as well as change the environment for the sample of the subjects in terms of practicing in the gym and then go to the swimming pool and then give special medical ointments, which helped the desire to perform exercises and create a spirit of competition and the goal of research to The preparation of special exercises and the use of swimming and medical ointments and health food systems for specific areas in the body to remove body wrinkles after weight loss and know the effect of special exercises to tighten the layers of skin and body beauty after weight loss. The hypothesis was research, to special exercises and various means, such as swimming, the use of medical ointments and health food systems, has a positive effect on skin layers and body mass after weight loss. Different areas of the body were selected and the areas where the fat accumulation was increased after taking the opinions of experts and specialists. The tests were carried out in the pretest and the training program was implemented and followed closely in the form of two groups take the usual training program and the other exercises were used to develop muscle strength and swimming and put ointments after and after the end of the application of the training program was conducted after the tests and after the results were calculated and analyzed and discussed the development of the members of the research sample through the loss of weights of their bodies as well as raising their physical capacity and development of the first experimental group that used the training program prepared by researchers and improve their body through a decrease physical wrinkles and then the researchers concluded that exercise contributes significantly to maintaining fitness and increase physical capacity.Keywords: Special exercises, Weight loss skin wrinkles and body beauty.